2009
DOI: 10.1111/j.1096-3642.2009.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic revision of the genus Everettia Godwin-Austen, 1891 (Mollusca: Gastropoda: Dyakiidae) in Sabah, northern Borneo

Abstract: The species of the snail genus Everettia in the Malaysian state of Sabah are superficially similar and difficult to distinguish by their shells. This paper presents new data on the taxonomy and distribution of Everettia in Sabah that have accumulated since the revision by Godwin-Austen in 1891. By using morphological and molecular phylogenetic approaches, we reveal at least seventeen species of Everettia in Sabah, of which eleven are new to science, namely: Everettia layanglayang sp. nov., Everettia lapidini s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
4
26
2
Order By: Relevance
“…As already known from morphological descriptions [36], the glands of the dart sac are attached at its posterior end via ducts that feed into the dart sac. These ducts and some of the glandular tissue are shown in Figure 2A.…”
Section: Resultsmentioning
confidence: 98%
“…As already known from morphological descriptions [36], the glands of the dart sac are attached at its posterior end via ducts that feed into the dart sac. These ducts and some of the glandular tissue are shown in Figure 2A.…”
Section: Resultsmentioning
confidence: 98%
“…The current classification of many Cyclophorids was based solely on morphology characteristics where its reliability remains doubtful as this taxa possesses exceptionally diverse variations in morphology. Past research has shown that molecular phylogenetic analyses could provide insights into the taxonomy of morphologically-ill land snails in this region (Nantarat et al, 2014a(Nantarat et al, , 2014bLiew et al, 2009;Liew et al, 2014). This study presents the first molecular phylogeny investigation on genus Leptopoma in Sabah, one of the understudied taxa within Cyclophoridae, and examines the concordance between morphology and phylogeny as well as geographical variations in shell form.…”
Section: Discussionmentioning
confidence: 96%
“…High values of genetic divergence were reported for the land slug Phyllocaulis (13.1%) (Gomes et al 2010) and between congeneric species of Ariophantidae and Dyakiidae (4.3 to 10.1%) (Abu-Bakar et al 2014). Moreover, Liew et al (2009) reported divergence values of 5% to 25% within Everettia spp. (Dyakiidae).…”
Section: Discussionmentioning
confidence: 99%